PERBANDINGAN KEKUATAN SAMBUNGAN BAMBU MENGGUNAKAN PENGISI MORTAR DENGAN ISIAN UJUNG DAN ISIAN SAMPING - Ida Nugroho Saputro (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2013)
This research about strength of bamboo connection using mortar filler to its tension strength using 1bolt with 12 mm diameter. Mortar filler has ratio of cement to sand 1 : 3 with water cement ratio 0,6. Testing ofconnection strength conducted with angle of pulling 0°, 30°, 60°, and 90° to bamboo fiber direction. In addition,to identify effect of clamp usage and filler hole position. The testing conducted with hydraulic jack that installedto loading frame. Result of this research showed that clamp usage lead to strength increase 13,82%. Connectionstrength decrease happened as the angle of pulling more and more. The lowest strength with angle 90° is 8,34KN for side filler connection and 9,81 KN for edge filler connection. The highest of connection strength with angle0° is 25,51 KN for side filler connection and 28,45 KN for edge filler connection. The mortar filler hole positiondid not influence connection strength. Comparison between theory and experiment was adjacent, thereforeproposed equation can be used.